Culinary capital as female empowerment: a critical reading of select Indian tribal narratives - Sachdeva, Saru; Rani, Rekha (Penerbit Universiti Kebangsaan Malaysia, 2025)
Food has its own language and a system of communication. Every household has its unique way of preserving and maintaining its culinary capital and food culture, thus holding a unique language and heritage of the kitchen. Therefore, this unique language also helps establish and sustain gender and power relationships in the family and society. Thus, food helps in understanding the culture and history of a family, community, class or caste. However, the space in and of the kitchen is not just a space to own and control by women but also a space for camaraderie, women bonding and empowerment. Reading and critically analysing Indian tribal texts –They Eat Meat! by Hansda Sowvendra Shekhar, Civilising the Tastebuds by Techi Nimi, A Respectable Woman and A Terrible Matriarchy by Easterine Kire through the lens/idea of culinary capital, the present paper highlights how women use food and kitchen as power centres for women empowerment. The concept of culinary capital reads how food and culinary practices serve as the markers of sociocultural and hierarchical distinctions within a culture. This manifests in the preparation, consumption and presentation of food discussed by Tech Nimi in Civilising the Tastebuds while They Eat Meat! Offers resistance by women through the kitchen, A Terrible Matriarchy and A Respectable Woman show women's creativity and intelligence in food preparation. Subverting the power dynamics, a tribal woman transforms the kitchen from a given limited space to a space for exploring her creativity, sisterhood and resistance.